Optimization of the Search for Neuroprotectors among Bioflavonoids - Igor Belenichev; Victor Ryzhenko; Olena Popazova; Nina Bukhtiyarova; Nadia Gorchakova; Valentyn Oksenych; Oleksandr Kamyshnyi (MDPI AG, 2024)
For the first time, to optimize the creation of new neuroprotective agents based on bioflavonoids, we applied information technologies; these include docking analysis to calculate the binding of candidate molecules to the pharmacological target protein transthyretin as well as a program of virtual screening of NO scavengers. As a result of this approach, the substance catechin was isolated from candidate molecules-quercetin, catechin, Epicatechin gallate, Epicatechin, Procyanidin B1, Procyanidin B2, Procyanidin B3, and Catechin-3-gallate-according to docking analysis. As a result of virtual screening, catechin was identified as a potential NO scavenger (55.15% prediction). The results of the prediction were confirmed by in vitro experiments. Course administration of catechin to animals with experimental multiple sclerosis (MS) against the background of methylprednisolone administration completely eliminated lethal cases, reduced the number of diseased animals by 20% as well as prevented the development of severe neurological symptoms by 20% (compared to the methylprednisolone group) and by 60% compared to the control group. Course administration of catechin with methylprednisolone leads to a decrease in the neurodegradation markers in the cytosol of rats, with EAE: NSE by 37% and S-100 by 54.8%. The combined administration of methylprednisolone significantly exceeds the combination of methylprednisolone with the reference drug mexidol by the degree of NSE reduction. The obtained results indicate a significant neuroprotective effect of ocular combinations of methylprednisolone and catechin. The above-mentioned confirms the correctness of the bioflavonoid selection with the help of a virtual screening program.